PREPARASI DAN EVALUASI EKSIPIEN KO-PROSES PATI SINGKONG-KITOSAN YANG DIBUAT SECARA SPRAY DRYING - Wicaksono, Yudi; Witono, Yuli; Herlina, .; Nuri, . (Jurnal Farmasi Indonesia, 2010)
Tapioca starch is pharmaceutical excipient for diluent of tablet with poorly in flowability and compactibility. Chitosan is biodegradle polymer and have been widely used for pharmaceutical excipient. It have a marked tendency to plastic deformation, and a good compression behaviour. Co-processing is the one of the most widely explored and commercially utilized method for the preparation of directly compressible excipient. The aim of study was to develop direct compression excipient of the tapioca starch-chitosan using co-processing method by spray drying. Co-processed excipient were prepared by spray drying suspension of feed of the chitosan - tapioca starch in different ratios (1:2, 1:3 & 1:4). The co-processed excipients were evaluated for morphology, moisture content, angle of repose, flow rate of granules, bulk density, tapped density, Carrâ??s index, viscosity and melting point. The result showed co-processed excipient of tapioca starch-chitosan have spherical in shape, moisture content in the range of 4.04 â?? 5.39 %, angle of repose was found to be <Â  380, flow rate of granules in the range of 1.3 â?? 3.8 g/s, bulk density in the range of 0.46 â?? 0.57 g/ml, tapped density in the range of 0.57 â?? 7.58 g/ml, Carrâ??s index in the range of 19.16-27.11 %, viscosity in the range ofÂ  1.77-2.17 mPas and melting point in the range of 195.33-198.50 0C. ABSTRAK Pati singkong adalah eksipien farmasi untuk pengisi tablet dengan sifat alir dan kompaktibilitas tidak baik. Kitosan adalah polimer biodegradabel dan telah digunakan secara luas untuk eksipien farmasi. Kitosan mempunyai kecenderungan untuk deformasi plastis dan sifat kompresi yang baik. Ko-prosesing adalah salah satu metode komersial yang digunakan secara luas untuk pembuatan eksipien cetak langsung. Â Tujuan dari penelitian ini adalah untuk mengembangkan eksipien cetak langsung dari pati singkong-kitosan dengan menggunakan metode ko-prosesing secara spray drying. Eksipien ko-proses disiapkan dengan menspray drying suspensi cairan umpan dari kitosan-pati singkong dalam perbandingan yang berbeda (1:2, 1:3 dan 1:4). Eksipien ko-proses dievaluasi untuk morfologi, kandungan lembab, sudut diam, kecepatan alir granul, berat jenis nyata, berat jenis mampat, indeks Carr's, viskositas dan titik lelehnya. Hasil menunjukkan eksipien ko-proses pati singkong-kitosan mempunyai bentuk sferis, kandungan lembab dalam rentang 4,04 â?? 5,39 %, sudut diam <380 , kecepatan alir granul dalam rentang 1,3 â?? 3,8 g/s, berat jenis nyata dalam rentang 0,46 â?? 0,57 g/ml, berat jenis mampat dalam rentang 0,57 â?? 7,58 g/ml, Indeks Carr's dalam rentang 19,16-27,11 %, viskositas dalam rentangÂ  1,77-2,17 mPas dan titik leleh dalam rentang 195,33-198,50 0C.